The Meaning of "Spirituality": a discussion with its starting point in an investigation among alternative therapists - Ahlin, Lars (Implicit religion, 2008)
In the contemporary Western world one can observe a remarkable popularity of the term "spirituality." However, there are different understandings of the concept. Among other things, discussion is occupied with the problem of how to differentiate "spirituality" from "religiosity." However, my intention here is not to present yet another definition, or to give guidelines on how to differentiate it from "religiosity." My objective is much more limited. On the one hand I intend to propose some beliefs and practices that ought to be included in a substantive definition of "spirituality." On the other hand I want to discuss some problems involved in this enterprise. My approach is indirect. I have not asked any respondents how they perceive or define "spirituality." So it may be asked: How is it possible to say what beliefs and practices people refer to, if you don't ask them directly?